Implementation of mobile APP service in an electronic tax invoice - Seop Shim, Myeong (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study is designed to carry out effective work such as electronic tax invoice issuing,transfer and retrieval for National Tax Administration, tax invoice checking in sales and purchase through smartphone with no regard to time and place according to the development of issuing in electronic tax invoice based on smartphone mobile application against electronic tax invoice based on existing Web. Methods/Statistical analysis: Data analysis of existing electronic tax invoice and database analysis of electronic tax bill based on existing Web for the purpose of application development in iphone and Android based phone. FindingsSmartphone based functions of how to write or issue or check a tax invoice as well as supporting customer are implemented in this study in order for the target of design and building application in smartphone for Web based electronic tax invoice through analysis of database in existing Web based electronic tax invoice. Improvements/Applications: Services that can deliver electronic tax invoice issuingmore quickly and rapidly to a lot of users having restrictions in time and place who are related in wholesale and retail dealers, distribution dealers, and fording agent are able to provide through application of electronic tax invoice issuing based on smartphone which is developed in this study.